Global Trends and Emerging Themes in Public Sector Innovation Research: A Bibliometric Analysis - Gusti Naufal Rizky Perdana; Ni Wayan Desi Budha Jayanti; Yaen Miftakhul Laily; Muhammad Khafid Ainul Yaqin (Golden Ratio of Data in Summary, 2026)
Public sector innovation has become an increasingly important topic in public administration due to the growing demand for adaptive governance, digital transformation, and improved public service delivery. However, the rapid expansion of the literature has made it difficult to identify the intellectual structure, major trends, and emerging themes within the field. This study aims to map the evolution of public sector innovation research through a bibliometric analysis of 534 Scopus-indexed publications published between 2015 and 2025. The analysis was conducted using VOSviewer to examine publication trends, influential authors, countries, affiliations, citations, and keyword networks. The results reveal a substantial growth in public sector innovation research over the last decade, with significant contributions from the United States, the Netherlands, the United Kingdom, Canada, and Australia. Co-creation, collaborative innovation, governance, and digital transformation emerged as the most influential themes, while recent studies increasingly focus on digital governance, technology adoption, transparency, and collaborative approaches. This study contributes by providing a systematic overview of the field’s intellectual landscape and identifying emerging research directions that can inform future studies and public sector innovation policies.